Regional differences and dynamic evolution in the resilience of public-private partnership projects: Evidence from the China - Jiangtao Chi; Yi Huang; Xin Li; Jiaying Li; Zihan Xia; Feiwu Ren; Xiangyun Xu; Jinbo Song; Yanwei Wang (Project Leadership and Society)
In the context of high-quality development and in the face of uncertainties and risks from economic, social and political sources, we aim to understand the resilience of public-private partnership projects in megaprojects, and to improve their ability to effectively manage adversity and optimize resource allocation. And by utilizing these insights and adopting proactive strategies, we enable stakeholders to navigate uncertainty more effectively and contribute effectively to high-quality development. Based on 2005–2020 provincial panel data in China, we explore the regional differences, dynamic evolution and convergence in the resilience of public-private partnership projects using an integrated approach combining entropy weight method, Dagum Gini coefficient, kernel density estimation and spatial econometric modeling. The results of the study show that: The resilience of public-private partnership projects in the nationwide and in East, Central, West and Northeast is steadily increasing, with higher in the East and weaker in the West; The differences between the four regions show a gradual widening trend, but decrease towards the end of the study period, and was accompanied by trailing and polarization across the country and the regions; There is absolute β convergence in the resilience of public-private partnership projects across the country and in the four regions.